2018
DOI: 10.1002/hep.29759
|View full text |Cite
|
Sign up to set email alerts
|

Liver‐specific deficiency of unc‐51 like kinase 1 and 2 protects mice from acetaminophen‐induced liver injury

Abstract: Together, these findings reveal an important role of Ulk1/2 for APAP-induced JNK activation and liver injury, and understanding of this regulatory mechanism may offer us new strategies for prevention and treatment of human APAP hepatotoxicity. (Hepatology 2018;67:2397-2413).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 47 publications
(147 reference statements)
1
22
0
Order By: Relevance
“…More recently, Sun et al found that ULK1/ULK2 double KO mice are also resistant to APAP‐induced liver injury. Surprisingly, ULK1/ULK2 double KO mice have intact hepatic autophagy and therefore no p62‐mediated Nrf2 activation was found in ULK1/ULK2 double KO mice . Instead, ULK1 is required for the maximum activation hepatic JNK in response to APAP treatment.…”
Section: Autophagy Regulates Gsh Biosynthesis and Jnk Activationmentioning
confidence: 98%
See 1 more Smart Citation
“…More recently, Sun et al found that ULK1/ULK2 double KO mice are also resistant to APAP‐induced liver injury. Surprisingly, ULK1/ULK2 double KO mice have intact hepatic autophagy and therefore no p62‐mediated Nrf2 activation was found in ULK1/ULK2 double KO mice . Instead, ULK1 is required for the maximum activation hepatic JNK in response to APAP treatment.…”
Section: Autophagy Regulates Gsh Biosynthesis and Jnk Activationmentioning
confidence: 98%
“…Mechanistically, APAP inhibits mTORC1 resulting in the release of activated ULK1, which then directly phosphorylates and increases the kinase activity of mitogen‐activated protein kinase kinase 4 and 7 (MKK4/7), the upstream kinases and activator of JNK. Liver‐specific ULK1/ULK2 double KO mice have impaird APAP‐induced JNK activation and are thus resistant to APAP‐induced liver injury . Taken together, it seems that chronic inhibition of autophagy may lead to compensatory non‐canonical activation of Nrf2 and protects against APAP‐induced liver injury.…”
Section: Autophagy Regulates Gsh Biosynthesis and Jnk Activationmentioning
confidence: 98%
“…70 Moreover, unexpectedly, recent data also demonstrate that by promoting activation of c-Jun N-terminal kinase signalling the kinase activities of ULK1/2 are essential in APAP-induced liver injury, independently of their activity in autophagy. 71 Based on the data from these studies, it cannot be excluded that autophagy-dependent and independent ULK1 pathways result in opposing regulation of APAP-induced liver injury.…”
Section: Modulation Of Autophagy For Therapeutic Purposes: a Promisinmentioning
confidence: 99%
“…65 More recently, unc-51 like autophagy activating kinase (ULK1/2) was identified as another upstream kinase that contributes to JNK activation through phosphorylation of MKK4/7. 66 Activation of JNK occurs early after APAP overdose, with a dose of 300 mg/kg resulting in JNK activation within 1 hour in the cytosol. 62 In addition, glycogen synthase kinase-3β (GSK-3β), a major regulator of glycogen synthase, has also been implicated in JNK activation after APAP.…”
Section: Amplification Of Mitochondrial Dysfunction and Downstream Simentioning
confidence: 99%